Photo Alignment Behaviour of Polyethene Imine Having Cyano Azobenzene Side Chain (Dhaka University Journal of Science, 2015)
New type of polyethene imine having cyano (-CN) side chain through six methylene spacer group (PEI6C) was successfully synthesised and characterised. The effect of reaction parameters on degree of substitution of PEI6C was also studied and the reaction conditions were optimised. Photochemical as well as photoorientational behaviour of the polymer were investigated. PEI6C in solid film exhibited photoresponsive properties upon irradiation with UV and visible light. PEI6C film also exhibited reversible molecular orientation from random state to out-of-plane and from out-of-plane to random state upon non-polarised visible and UV light irradiation.Dhaka Univ. J. Sci. 63(2): 67-72, 2015 (July)